Synchrotron radiation X-ray phase micro-computed tomography as a new method to detect iron oxide nanoparticles in the brain. - Marinescu, M; Langer, M; Durand, A; Olivier, C; Chabrol, A; Rositi, H; Chauveau, F; Cho, T H; Nighoghossian, N; Berthezène, Y; Peyrin, F; Wiart, M (Molecular Imaging & Biology, 2013)
Purpose: The purpose of this study was to introduce synchrotron radiation X-ray phase computed tomography (SR-PCT) as a new method of visualizing ultrasmall superparamagnetic particles of iron oxide (USPIO) distribution into the brains of mice with neuroinflammation.Procedures: The sensitivity of the technique was assessed by performing back-to-back SR-PCT and magnetic resonance imaging (MRI) in mice stereotaxically injected with a range of USPIO concentrations. Eight mice with cerebral ischemia were then intravenously injected with USPIOs and imaged back-to-back with MRI and SR-PCT.Results: SR-PCT proved sensitive enough to detect iron in nanomolar quantities. In stroke-induced animals, SR-PCT showed hyperintense areas in the regions of MR signal loss and immunostaining for macrophages. SR-PCT, moreover, identified brain anatomy as clearly as histology, without the need for sectioning or staining, with an examination time of 44 min per brain at an isotropic spatial resolution of 8 μm.Conclusion: SR-PCT has potential for cellular imaging in intact brain, with unequaled neuroanatomy.